The musical experience of the improvisors of the andean area and the colombian caribbean (2020)
In the music world, the importance of improvisation as a means to promote the active and creative thinking of the musician is widely recognized. Its practice involves, among other things: making decisions in real time, listening to others, predicting and experimenting with new structures and musical organizations and carrying out sensory and perceptual adjustments necessary for an adequate interpretation. This article synthesizes the main conceptions and mechanisms developed by a representative sample of Colombian improvisers in their respective contexts. For this, using an ethnomusicological methodology centered on case study, the authors examine how these musicians conceive improvisation based on their life experiences. The study shows how the instrumental improvisation observed in traditional repertoire is carried out thanks to a previous training within each cultural framework and by the usage of some raw materials and procedures.